The Relationship Between Salary, Promotion, Career Planning and Career Development Among Private College Lecturers - Hazelena Dewi Fatahul Ariffin; Panji Hidayat Mazhisham (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
A career in teaching can be highly rewarding for those professionals interested in positively influencing the future of students. Advancement opportunities for teachers typically include promotions and role transfers to other educational positions with more responsibility in terms of leadership, administration or specialization. While pursuing advancement sometimes requires teachers to earn additional certifications or degrees, these opportunities can offer professional development and higher rates of compensation. This study aims to investigate the relationship between salary increase, promotion, career plans, and career development among academics at a private Islamic institution in Selangor. Self-Administered questionnaires were distributed to collect information from the respondents in understanding their reward, promotion, and career plan and relating them to their career advancement. The findings suggest that salary increase, career promotion, career planning, and career development have a favorable and significant link. In summary, it can be said that career planning and pay go hand in hand with career advancement.